Peran UPTD Perlindungan Perempuan dan Anak dalam Menangani Korban Kekerasan pada Anak di Kabupaten Sidoarjo - Devina Agnes Berlian Atika Putri; Tukiman Tukiman (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
There are always physical and psychological repercussions of violence towards children. A child's identity might be harmed if numerous child victims in the Sidoarjo Regency do not receive particular aid and therapy. In an effort to protect child victims of violence, organizations such as the Sidoarjo Regency Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) have been formed. This research aims to explain how the Sidoarjo Regency Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) helps children who are disadvantaged. In addition, this research aims to describe the difficulties faced by UPTD PPA when providing assistance to children in Sidoarjo Regency who are victims of violence. In this research, qualitative descriptive methodology was used. Researchers collect data, observations, interviews and documentation to obtain comprehensive and detailed information. The Director of UPTD PPA, legal advisors, psychiatric counselors, people who have used UPTD PPA services, and clients all participated in this research. (1) The responsibility of the UPTD PPA in handling victims of violence against children is based on six responsibilities, including: a) processing public complaints; b) victim outreach; c) case management; d) provide temporary housing; e) mediation; and f) provide support to victims. (2) The absence of human resources in the UPTD PPA Sidoarjo Regency, namely drivers for pick-up and drop-off services as well as in the role and function of community complaint services and outreach to victims, which are still subpar, is a challenge for the UPTD PPA.